Off-texts in television reportages as a variety? Characteristics of a professional television language in the context of current changes - Giessen, Hans (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
Television language – i.e. not on-screen conversations, but written texts combined acoustically with moving images – has specific properties that suggest it is a genre in its own right. Professional television writers know and use the characteristic rules of this genre. In a first step, television language will be described. In a next step, a significant change in the use of this specific genre language will be described. Its cause is technical change which in turn has had social and economic consequences. The focus lies on television texts for digital channels whose authors have no journalistic training, neither know the reasons for the rules of the television language genre, nor do they know how to apply them. The hypothesis would therefore be that a difference in the use of language can be observed between the authors of professional television news and the authors from the context of the digital providers. This will be shown by means of an empirical comparison of news from a large public broadcaster and a small private (regional) digital broadcaster.
Keywords: television texts; grammar; lexis; media adequacy; mmodalityulti